Clinical and radiographic evaluation of a new stain-free tricalcium silicate cement in pulpotomies - Suéllen Priscilla Rodrigues de LIMA; Greissy Lopes dos SANTOS; Antonio FERELLE; Solange de Paula RAMOS; Juliano Pelim PESSAN; Cássia Cilene DEZAN-GARBELINI (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The aim of this study was to evaluate and compare the clinical and radiographic success rates of pulpotomies in primary molars using a new stain-free tricalcium silicate cement (Bio-C Pulpo) versus a conventional white MTA (MTA Angelus) as a pulpotomy medicament for primary teeth. Seventy primary teeth in 33 patients were randomly divided into two groups, MTA Angelus (n = 34) and Bio-C Pulpo (n = 36). Clinical and radiographic follow-up examinations were conducted at seven days (except radiographic follow-up), and at one, three, six and 12 months. At 12 months, the clinical success rate of the MTA Angelus group was 100 percent (28 out of 28), and the radiographic success rate was 100 percent (28 out of 28). In comparison, the clinical success rate for the Bio-C Pulpo group was 100 percent (29 out of 29), and the radiographic success rate was 100 percent (29 out of 29). No significant differences were found between the groups at any follow-up evaluation. According to Fisher´s exact test, a significant difference was observed between the pulpotomy agent and tooth discoloration (p < 0.001). The success rates were 100% for the Bio-C Pulpo group, with no case of discoloration, and 10.31% for the MTA Angelus group. Both MTA Angelus and Bio-C Pulp pulpotomy medicaments are appropriate options for pulpotomies in primary teeth, and enable high clinical and radiographic success rates. However, more long-term studies are required to test the new Bio-C Pulpo medicament.